2019
DOI: 10.1108/ijlss-03-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Applying lean six sigma to grading process improvement

Abstract: Purpose The purpose of this paper is to explain how the lean six sigma (LSS) methodology can be implemented in a teaching context to positively impact the experience of both the instructor and student. The paper focuses on: describing the application of the LSS methodology in streamlining the grading process; reporting the findings; and examining possibility of deploying the LSS methodology in additional aspects in the education sector. Design/methodology/approach The observations presented in this paper ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Some applications approach the library sector (Sunder, 2016) moving offices cost reduction (Wheeler-Webb and Furterer, 2019) and improving the teaching program development (Thomas et al. , 2017), and the educational experience between the student and teacher (Oliver et al. , 2019) and services in general (Li et al.…”
Section: Case Studies Per Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Some applications approach the library sector (Sunder, 2016) moving offices cost reduction (Wheeler-Webb and Furterer, 2019) and improving the teaching program development (Thomas et al. , 2017), and the educational experience between the student and teacher (Oliver et al. , 2019) and services in general (Li et al.…”
Section: Case Studies Per Areamentioning
confidence: 99%
“…Oliver et al. (2018) approached the problem faced by teachers in an HEI related to the unusually long hours used to grading homework.…”
Section: Case Studies Per Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the employability skills of business school graduates have become a very important issue (Johnson et al, 2016). Universities are increasingly working to systematically improve the higher education process and its outcomes (Oliver et al, 2019). Scholars have applied many concepts and methodologies from the business world to improve the institutions of higher education, such as total quality management (Psomas and Antony, 2017), quality assurance (Seyfried and Pohlenz, 2018), quality function deployment (Aytac and Deniz, 2005), balanced scorecard (Sudirman, 2012), six sigma (Thomas et al, 2017), kaizen (Emiliani, 2005) and lean thinking (Emiliani, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the AACSB has indicated that business curricula must be improved continuously (Nonet et al, 2016). Oliver et al (2019) argue that this continuous improvement requires a proper systematic mechanism for improvement. One of the systematic mechanisms to improve the business school curriculum is to emphasize value-added activities and remove non-value-added activities.…”
Section: Introductionmentioning
confidence: 99%